VERTICAL DISTRIBUTION OF 137Cs IN SOILS OF FRESH AND WET SUBORS OF UKRAINIAN POLISSIA - Melnyk-Shamrai, V. V. (Scientific Progress & Innovations, 2021)
The modern vertical distribution of 137Cs in forest soils of different types of forest growth conditions of Ukrainian Polissya has been analyzed. Investigations were carried out on the sampling areas which were laid down in Narodyshy Forestry. Soil profiles were laid down in typical places in compliance with the standard requirements for conducting these studies. It is possible to establish the same regularities in radio-nuclide distribution, when studying the 137Cs specific and total activity values in the layers of forest floor of fresh and wet subors of Ukrainian Polissia. Thus, the forest floor in the studied types of forest growth condi-tions by the value of the analyzed parameters can be placed in the following order: decomposed layer > semi-decomposed layer > modern precipitation. The 137Cs specific activity values in the soil mineral layers are characterized by significantly smaller values compared to the forest floor, and opposite patterns are ob-served for the total radionuclide activity. The vertical distribution of radionuclides in the soil mineral layers is exponential in nature, and the radionuclide specific and total activity is reduced with depth. It has been established that the main content of 137Сs is concentrated the in 0–24 cm of the soil mineral layer for both types of forest growth conditions. The share of 137Cs gross reserve in the forest floor and soil mineral layers made 18.74 % and 81.26 % in wet subors, and fresh subors – 25.83 % and 74.14 %, respectively. The 137Cs total activity relative content in the forest floor and mineral layers within the limits of one trophotope was analyzed. The analysis of 137Cs gross distribution in the layers of forest floor has shown that in wet subors it is 1.4 times less than in fresh subors. The maximum 137Cs content in the soil mineral layers was observed in the layer of 0–4 cm: in fresh subors it made 24.0 %, and in wet subors – 27.4 %. In the 0–20 cm mineral lay-er of fresh subors the radionuclide share made 51.7 %, while in wet subors it was 1.3 times higher, respec-tively. The reliability of the obtained results is confirmed by one-way analysis of variance at 95 % confi-dence level. Thus, according to the obtained results, it can be maintained that in wet subors there was more intensive 137Cs redistribution between forest floor and soil mineral layers than in fresh subors.